(untitled) (SCIENCE TIME JOURNAL, 2025)
The article is devoted to the study of the effectiveness of developmental therapy technologies in preparing preschool children with dysarthria for literacy education. The results of the study showed that developmental therapy exercises significantly increase the level of speech motor skills, phonemic perception, speech breathing and literacy readiness in children. At the same time, psychological support increases children’s motivation and reduces logophobia and speech avoidance behavior.